Reconstruction of Intrapelvic Defects Using the Free Anterolateral Thigh Flap: Expanding the Traditional Algorithm. Issue 5 (May 2020) - Wong, Alvin; Sbitany, Hani
Abstract : Background: Reconstruction of intrapelvic soft tissue defects traditionally relies on regional pedicled myocutaneous flaps. However, there remain situations in which local options are unavailable. We review our experience treating intrapelvic defects with the anterolateral thigh (ALT) microvascular free flap. Methods: A retrospective, institutional review was conducted from 2014 to 2018 of patients undergoing microvascular ALT flap reconstruction of intrapelvic defects. Four patients were identified in this cohort out of 92 total pelvic reconstruction cases. Results: All patients underwent abdominoperineal resection (APR) for rectal cancer treatment. In the two male patients, pelvic abscesses and bladder leak necessitated soft tissue reconstruction after radiation and APR. In both, regional tissue options were unavailable, and a buried ALT free flap was used for soft tissue reconstruction. Both female patients developed rectovaginal fistulas secondary to their tumor burden, necessitating posterior vaginal wall resections. Prior surgical scars and ostomies made abdominal wall tissue unavailable; thus, free ALTs were used to eliminate intrapelvic dead space and reconstruct the posterior vaginal wall. In all cases, recipient vessels were the deep inferior epigastric artery and vein. Flap survival was 100%. Conclusions: Pelvic reconstruction has traditionally been addressed with local/regional pedicled flaps. In cases where these are unavailable, the free ALT flap is a versatile option when buried for intrapelvic reconstruction or posterior vaginal wall lining. We also propose updating Cordeiro et al.'s classic vaginal defect reconstruction algorithm to include the free ALT flap for type IB cases in which the rectus abdominis is unavailable.